Insecticidal activity of the ethanolic extract from Croton species against Plutella xylostella L. (Lepidoptera: Plutellidae) (2018)
The objective of this work was to study the effect of ethanolic extracts from different parts of Crotonspecies on the diamondback moth (Plutella xylostella L.). Extracts from the leaves of Croton rhamnifoliusH.B.K., Croton jacobinensis Baill., Croton sellowii Baill. and Croton micans Muell. C. rhamnifolius had the most lethal effect (LC50 = 14.95 μg mL-1), followed by C. rhamnifolius (stem), C. jacobinensis (stem),C. jacobinensis (leaf), C. sellowii (leaf) and C. sellowii (stem) with LC50 values of 42.40, 116.21, 183.85, 801.36 and 1252 μg mL-1, respectively. Plutella xylostella larvae fed kale disks with all extracts, exceptC. sellowii (stem), exhibited prolonged larval duration. None of the extracts affected the duration of the pupal stage of the moth.